The process of formation of a movement in Burma - Mо'ydinov Muhammadali (Global Scientific Publishing, 2023)
This article provides information about the emergence of the Jadidism movement in Turkestan, the spread of enlightenment, the nature of this movement as a movement of national awakening, and its role in its development.
Keywords: Jadid; press; colonialism; Behbudi